1980
DOI: 10.2337/diab.29.12.1036
|View full text |Cite
|
Sign up to set email alerts
|

Type I (Insulin-dependent) Diabetic Multiplex Families: Mode of Genetic Transmission

Abstract: SUMMARYHLA genotypes have been analyzed in 120 classic type I (insulin-dependent) diabetic sib pairs with an age of onset below 16 yr reported to the British Diabetic Association register (1972-78). By this age, siblings of diabetic children are 26 times more likely to develop type I diabetes than other children. There is a highly significant disturbance in the zygotic assortment of HLA haplotypes in these sib pairs, providing conclusive evidence for the existence of major susceptibility genes in the HLA compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…For example, for IDDM, data are compatible with a recessive but not with a dominant mode of inheritance for the HLA linked susceptibility gene (200,219). On the other hand, the data on multiple sclerosis are consistent with both dominant and recessive modes of inheritance.…”
Section: Sib Pair and Related Methodssupporting
confidence: 67%
“…For example, for IDDM, data are compatible with a recessive but not with a dominant mode of inheritance for the HLA linked susceptibility gene (200,219). On the other hand, the data on multiple sclerosis are consistent with both dominant and recessive modes of inheritance.…”
Section: Sib Pair and Related Methodssupporting
confidence: 67%
“…The inheritance of type 1 diabetes is genetically determined, although in a complex manner. In humans, two type 1 diabetes susceptibility genes have been studied in great detail: the HLA region on chromosome 6p21, IDDM1 (1)(2)(3), and the insulin gene region, IDDM2, on chromosome 11p15 (4 -9). IDDM1 and IDDM2 contribute 42 and 10%, respectively, to the familial inheritance of the disease, and it can be further extrapolated that while other type 1 diabetes susceptibility genes exist, none can have the relatively large contribution described for IDDM1 (9,10).…”
mentioning
confidence: 99%
“…In contrast, B 18 without CW5 is not associated with BfF1. Furthermore, the frequency of the BfF1-B 18-CW5 haplotype in the probands was similar in families with one diabetic child and in families with two or more affected children, confirming that there is no difference in HLA susceptibility between 'sporadic' cases and those families with multiple affected siblings [13]. It is generally agreed that the Bf system is determined by one locus with four alleles, and that the Bf locus lies between HLA-B and -D. The HLA-C locus is also very close to HLA-B, but on the other side of it.…”
Section: Discussionmentioning
confidence: 59%
“…We have already shown that the HLA characteristics of these two family studies are very similar [13]. Because the Bf association is also similar in these two family studies, the data for the probands have therefore been combined (Table 1).…”
Section: Analysis Of the Hla Association With Bff1mentioning
confidence: 95%
See 1 more Smart Citation